2016
DOI: 10.1016/j.ajpath.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

α4-Integrin Antibody Treatment Blocks Monocyte/Macrophage Traffic to, Vascular Cell Adhesion Molecule-1 Expression in, and Pathology of the Dorsal Root Ganglia in an SIV Macaque Model of HIV-Peripheral Neuropathy

Abstract: Traffic of activated monocytes into the dorsal root ganglia (DRG) is critical for pathology in HIV peripheral neuropathy. We have shown that accumulation of recently recruited (bromodeoxyuridine þ MAC387 þ ) monocytes is associated with severe DRG pathology and loss of intraepidermal nerve fibers in SIV-infected macaques. Herein, we blocked leukocyte traffic by treating animals with natalizumab, which binds to a4-integrins. SIV-infected CD8-depleted macaques treated with natalizumab either early (the day of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…CD14 + CD16 + monocytes are key mediators of HIV neuropathogenesis ( 11 , 12 , 21 , 37 , 38 , 46 , 51 53 ). They transmigrate across the BBB in response to chemokines, including CCL2, which is one of the proposed mechanisms of viral entry into the CNS ( 21 , 22 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…CD14 + CD16 + monocytes are key mediators of HIV neuropathogenesis ( 11 , 12 , 21 , 37 , 38 , 46 , 51 53 ). They transmigrate across the BBB in response to chemokines, including CCL2, which is one of the proposed mechanisms of viral entry into the CNS ( 21 , 22 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are still no therapies that decrease neuroinflammation and neurodegeneration mediated by HIV infection of the CNS. Whereas some therapeutic targets have been suggested, these do not prevent entry of CD14 + CD16 + monocytes specifically into the brain [23,[60][61][62]. We demonstrated in this study that CXCR7 is expressed on the cell surface of CD14 + CD16 + monocytes, that it is higher in expression on CD14 + CD16 + monocytes than on CD14 + CD16 2 monocytes, and that it is increased on the surface of CD14 + CD16 + monocytes from HIV-infected individuals compared with those cells from uninfected people.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally,CD137 signaling regulates trafficking of activated macrophage to dorsal root ganglia, leading to severe loss of intra-epidermal nerve fiber densit [28]. Recently, as a potential therapeutic approach, treatment with α4-integrin antibody has been found to rescue dorsal root ganglia fiber damage by block-ingthetraffickingofactivatedmonocyte/macrophage, but not T-lymphocyte [29]. Similar antibody treatment in another study has been found to decrease cardiac pathology by regulating monocyte/macrophage trafficking to the heart in SIV-infected primate model of HIV-AIDS [30].…”
Section: Neuro-muscular Complications In Hiv-associated Sensory Neuromentioning
confidence: 99%